Cross-country variations in sovereign wealth funds’ transparency - Cuervo-Cazurra, Alvaro; Grosman, Anna; Wood, Geoffrey (Springer, 2023)
We explore what drives variations in sovereign wealth funds’ (SWFs) transparency across countries. SWFs have emerged as an important instrument for governments to invest and manage excess funds. However, despite serving similar needs, there is much diversity in how they are governed from country to country. We integrate agency theory with the varieties of capitalism framework to propose that the country’s governance characteristics determine the extent of SWFs’ multi-level agency problem, that is, a conflict arising from politicians acting as intermediaries between the citizens who are the nominal owners and the funds’ managers. We find that the home country’s type and quality of government and the origin of the wealth drive cross-country variations in the transparency of the SWFs. These ideas are useful for government officials and practitioners involved in policy advisory or dealing with SWFs. We highlight and explain how SWFs differ significantly across countries and thus caution against the one-size-fits-all approach to providing suggestions for government officials to improve the workings of their SWFs. We suggest that government officials consider how the characteristics of the political system of the country of origin drive much of the strategic behavior of SWFs, particularly their transparency. Thus, a comprehensive upgrading of governance in the SWFs may be contingent on enhanced country-level governance.
Keywords: sovereign wealth funds; government; political system; transparency; agency theory; varieties of capitalism